Destiny, Being and the Empirical Law of Large Numbers - D’Amico, Rosario (Journal of Mathematical Economics and Finance, 2020)
The aim of this paper is to give a practical meaning to the term ”possible”, which can then become a useful reading key to attempt to decipher the nature and functioning of the so-called Being, that is, of being-in-itself, of the reality implied, of what there is behind what it is. Thanks to this hermeneutic tool together with the singular existential experience of Mister Tanat`o, the imaginary protagonist of this treatment, we will interpret the Being as all that is pre-destined - that is, as the set of fundamental conditions for (there to be) such being [essente] or nothingness - and sensitive reality as all that is destined - that is, as the rotation of the guided evolutions of the Being -. Finally, to confirm and investigate the results we have achieved, we will provide a solution both to the hypothetical paradox of prediction, in which the apparent antinomy lies in admitting that predictions can be subsequently falsified, and to an interesting probabilistic problem.